Swearing and Subtitling Strategies in Penyalin Cahaya: A Qualitative Case Study - Yuniar Ayu Andini; Todo Sibuea (Jurnal Bahasa dan Sastra, 2026)
Indonesian swear words frequently appear in everyday communication and serve various functions, such as expressing anger, stress, humor, or familiarity. In film subtitling, translating swear words can be challenging due to cultural differences that affect how emotional expressions are understood. This study aims to identify the types of Indonesian swear words and the subtitling strategies used to translate them into English in the Netflix film Penyalin Cahaya. This research employs a descriptive qualitative method by analyzing all sixteen  instances of swear words identified in the film's dialogue. The data are classified based on types of swearing and subtitling strategies. The findings reveal that the swear words fall into three categories: cathartic, abusive, and idiomatic swearing, with cathartic swearing being the most frequent. In terms of translation, three strategies are identified: direct translation, omission, and substitution. Substitution is the most commonly used strategy, indicating that the subtitler tends to adapt Indonesian swear words into culturally acceptable English expressions while maintaining the emotional meaning and communicative effect of the original dialogue. These findings offer a framework for understanding how cultural and pragmatic constraints shape subtitling decisions, with practical implications for subtitle editors working across culturally distant language pairs in the streaming industry.